THE EFFECT OF DIFFERENT AMOUNTS ADDITION OF SEAWEED (Eucheuma cottonii) FLOUR TOWARD CHARACTERISTICS OF CATFISH (Pangasius hypopthalmus) EMPEK-EMPEK QUALITY - Lily Afriyanti; Sumarto '; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was aimed to obtain the best amount of seaweed (Eucheuma cottonii) flour in processing of catfish (Pangasius hypophthalmus) empek-empek from organoleptic quality and chemical analysis aspects. The seaweed (Eucheuma cottonii) was obtained directly from seaweed cultivation in Tanjung Medang water of north Rupat, Bengkalis regency, Riau. This research used completely randomized design, one factor with four levels of treatment 0%, 10%, 15% and 20%. The results of the study was very significant effect on organoleptic value includes the appearance, taste, aroma, texture and chemical values which include water content, fat content, ash content, whereas the levels of protein and calcium were significantly different. Based on parameters tested, the best treatment was the catfish empek-empek with addition 10% of seaweed flour, with appearance (7.99) of light brown colour, fish flavor more pronounced (7.61), fish aroma (7.61), solid, compact and chewy texture (7.26), and 65.97% of water content, 14.10% of protein content, 7.65% of fat content, 4.86% of ash content and 17.18 mg / 100 g of calcium content.Keywords: Empek-empek, Pangasius hypopththalmus, Quality, characteristics, Eucheuma cottonii